Conversion to Resectability Using Transarterial Chemoembolization Combined With Hepatic Arterial Infusion Chemotherapy for Initially Unresectable Hepatocellular Carcinoma. Issue 2 (8th June 2021) - Li, Binkui; Qiu, Jiliang; Zheng, Yun; Shi, Yunxing; Zou, Ruhai; He, Wei; Yuan, Yichuang; Zhang, Yuanping; Wang, Chenwei; Qiu, Zhiyu; Li, Kai; Zhong, Chengrui; et al.
Abstract : Conventional transarterial chemoembolization (c-TACE), a common regimen for initially unresectable hepatocellular carcinoma, provides a chance of resection for 10% patients. This study found that TACE plus hepatic artery chemotherapy infusion (TACE-HAIC) had a higher conversion rate to resection, better survival outcome and comparable advent event, compared with c-TACE. Abstract : Objective: To evaluate whether this conversion rate to resectability could be increased when patients are treated with transarterial chemoembolization and hepatic arterial infusion chemotherapy (TACE-HAIC) using oxaliplatin plus fluorouracil/leucovorin. Background: Conventional TACE (c-TACE) is a common regimen for initially unresectable hepatocellular carcinoma (HCC), which converts to curative-intent resection in about 10% of those patients. It is urgent need to investigated better regimen for those patients. Methods: The data of 83 initially unresectable HCC patients were examined, including 41 patients in the TACE-HAIC group and 42 patients in the c-TACE group. Their response rate, conversion rate to resection, survival outcome, and adverse events were compared. Results: The conversion rate was significantly better in the TACE-HAIC group than in the c-TACE group (48.8% vs 9.5%; P < 0.001). The TACE-HAIC had marginal superiority in overall response rate as compared to c-TACE (14.6% vs 2.4%; P = 0.107 [RECIST]; 65.9% vs 16.7%; P < 0.001 [mRECIST], respectively). The median progression-free survival was not available and 9.2 months for the TACE-HAIC and cTACE groups, respectively (hazard rate [HR]: 0.38; 95% confidence interval [CI], 0.20–0.70; P = 0.003). The median overall survival was not available and 13.5 months for the TACE-HAIC and c-TACE groups, respectively (HR, 0.63; 95% CI, 0.34–1.17; P = 0.132). The 2 groups had similar rates of grade 3/4 adverse events (all P > 0.05). Conclusions: TACE-HAIC demonstrated a higher conversion rate and progression-free survival benefit than c-TACE and could be considered as a more effective regimen for patients with initially unresectable HCC. Future prospective randomized trials are needed to confirm it.